Methodological approaches to assessing the value of a business - Pribylnova, I. В.; Muzychenko, A. S. (ХНУРЕ, 2021)
Valuation of business – is the process of sighting the value of property of the enterprise on the date of valuation according to the method, transformed by regulations, which will lead to the practical activities of the appraiser.
Keywords: Valuation of business; property of the enterprise